2019
DOI: 10.1371/journal.pone.0219204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KRAS, NRAS and BRAF hotspot mutations detection for patients with metastatic colorectal cancer using direct DNA pipetting in a fully-automated platform and Next-Generation Sequencing for laboratory workflow optimisation

Abstract: Background Assessment of KRAS , NRAS ( RAS ) and BRAF mutations is a standard in the management of patients with metastatic colorectal cancer (mCRC). Mutations could be assessed using next-generation sequencing (NGS) or real-time PCR-based assays. Times to results are 1 to 2 weeks for NGS and 1 to 3 days for real-time PCR-based assays. Using NGS can delay first-line treatment commencement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…19 In fact, although most cases (95%) were diagnosed by the fully automated approach only, on some occasions, NGS was still carried out to refine uncertain results displaying RT-PCR curves of undetermined interpretation. 20 Moreover, not all clinically relevant biomarkers are testable by Idylla; as an example, automated assays for KIT and PDGFRA gene evaluations have not been developed yet. On the other sides, the disadvantage of the fully automated approach is the higher overall cost for a single patient.…”
Section: Discussionmentioning
confidence: 99%
“…19 In fact, although most cases (95%) were diagnosed by the fully automated approach only, on some occasions, NGS was still carried out to refine uncertain results displaying RT-PCR curves of undetermined interpretation. 20 Moreover, not all clinically relevant biomarkers are testable by Idylla; as an example, automated assays for KIT and PDGFRA gene evaluations have not been developed yet. On the other sides, the disadvantage of the fully automated approach is the higher overall cost for a single patient.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that BNA-clamp PCR using Sanger sequencing detects somatic mutations in KRAS, NRAS and BRAF with a high accuracy (42). Gilson et al (43) used DNA pipetted directly in the cartridge of the Idylla system, exhibiting a good sensitivity, specificity, reproducibility and limit of detection, and can be integrated in a laboratory workflow for samples with little tissue without compromising the further complete Table III. Gene mutation status and progression-free survival analysis of patients with metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that BNA-clamp PCR using Sanger sequencing detects somatic mutations in KRAS, NRAS and BRAF with a high accuracy ( 42 ). Gilson et al ( 43 ) used DNA pipetted directly in the cartridge of the Idylla system, exhibiting a good sensitivity, specificity, reproducibility and limit of detection, and can be integrated in a laboratory workflow for samples with little tissue without compromising the further complete tumor characterization using NGS. In the present study, the ABI PRISM 310 genetic analyzer system and Taqman genotyper v.1.6 software (Applied Biosystems; Thermo Fisher Scientific, Inc.) were used to perform accurate analysis using automated capillary electrophoresis for genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Gilson et al conducted a study using the Idylla real-time PCR platform to detect BRAF, NRAS, and KRAS mutations in 38 samples from patients with colorectal cancer. 70 All sample mutation statuses were previously confirmed using NGS as a reference. Eight specimens were selected to evaluate the sensitivity and 12 for the specificity for the identification of BRAF mutations using real-time PCR.…”
Section: Braf V600e Mutation Testing Methodsmentioning
confidence: 99%